Pengetahuan, Pemanfaatan Support System dan Kualitas Hidup Penderita Gagal Ginjal Kronis - Ali Akbar; Nurpratiwi Nurpratiwi; Mimi Amaludin (Universitas Malahayati Lampung, 2024)
ABSTRACT The high incidence of chronic kidney failure is the last stage of the stage of kidney failure. The course of kidney failure to reach the final stage is also influenced by the knowledge and use of all forms of support after someone is diagnosed with kidney failure. The support referred to generally leads to several components that can support health status such as biological, psychological, social, and spiritual support. To identify descriptions of knowledge, history of the use of support systems and quality of life of patients with kidney failure. This descriptive study was carried out from November 2022 to May 2023. A total of 65 respondents involved in this study were selected, namely chronic kidney failure patients undergoing hemodialysis at Yarsi Pontianak General Hospital. Respondents were selected by accidental sampling. The results of the study show an overview of the knowledge of respondents 100% have obtained health information about chronic kidney failure, information obtained from doctors (83.1%), received information after being diagnosed (75.4%), information in the form of signs and symptoms (73.8 %). Utilizing the support system, respondents were accompanied by family or relatives when given an explanation by health workers (90.8%) and most of them did not need further information about this disease (55.4%). An overview of the quality of life of patients with chronic kidney failure undergoing hemodialysis in the moderate category (55.4%) and in the good category (40.0%). Most of the respondents have a support system, have adequate knowledge and show that most hemodialysis patients have a good quality of life. Keywords: Knowledge, Support System, Quality of Life ABSTRAK Tingginya angka kejadian gagal ginjal kronis yang merupakan tahapan terakhir dari stadium gagal ginjal. Perjalanan penyakit gagal ginjal untuk sampai pada stadium akhir turut dipengaruhi oleh pengetahuan dan pemanfaatan segala bentuk dukungan setelah seseorang divonis menderita gagal ginjal. Dukungan sebagaimana dimaksud secara umum mengarah pada beberapa komponen yang dapat menunjang status kesehatan seperti dukungan biologis, psikologis, sosial, dan spiritual. Mengidentifikasi gambaran pengetahuan, riwayat pemanfaatan support system dan kualitas hidup penderita gagal ginjal. Penelitian deskriptif dilaksanakan pada bulan November 2022 sampai dengan Mei 2023. Sebanyak 65 Responden terlibat dalam penelitian ini yang dipilih yaitu pasien gagal ginjal kronis yang menjalani hemodilisa di RSU Yarsi Pontianak. Responden dipilih secara accidental sampling. Hasil penelitian menunujukkan gambaran pengetahuan respoden 100% telah memperoleh informasi kesehatan tentang gagal ginjal kronis, informasi diperoleh dari dokter (83,1%), menerima informasi setelah terdiagnosis (75,4%), informasi berupa tanda dan gejala (73,8%). Pemanfaatan support system, responden ditemani oleh keluarga atau kerabat saat diberikan penjelasan oleh tenaga kesehatan (90,8%) dan sebagian besar tidak memerlukan informasi lebih lanjut tentang penyakit ini (55,4%). Gambaran tentang kualitas hidup penderita gagal ginjal kronis yang menjalani hemodialisa pada kategori sedang (55,4%), dan pada kategori baik (40,0%). Sebagian besar responden memiliki memiliki support system, memiliki pengetahuan memadai dan menunjukkan bahwa sebagian besar pasien hemodialisis memiliki kualitas hidup yang baik. Kata Kunci: Pengetahuan, Support System, Kualitas Hidup